Behavior of composite columns repaired by CFRP and subjected to uniaxial and biaxial eccentric load. Issue 1 (1st January 2021) - Al-Adawy, Karim Salah; El.Shafey, Nasser F.; Kassem, Magdy E.
ABSTRACT: This paper presents an experimental program to study the behavior of short high strength concrete composite columns subjected to either uniaxial or biaxial eccentric loading. The paper also includes a study on a suitable repairing technique for those columns by using carbon fiber reinforced polymers. The experimental program divided into two phases, the first consists of studying the behavior of six high strength reinforced concrete composite columns, three of them subjected to uniaxial eccentric loading as well as the other three subjected to biaxial eccentric loading, while the second phase deals with the behavior of five columns from the first phase after repairing them by carbon fiber reinforced polymers and subjecting them to the same eccentric loading. The main variables were the load direction, the number of sheets of carbon fiber reinforced polymers used and their arrangements. A comparison between the behavior of each column before and after repairing, using different numbers and arrangements of sheets of carbon fiber reinforced polymer layers was made. The comparison showed that wrapping composite steel columns with carbon fiber reinforced polymers is considered a very effective technique for repairing.